Nilai Moral Tokoh Utama dalam Novel Peter karya Risa Saraswati - Dinda Putri Larassati (fakultas sastra, 2021)
This study aims to describe (1) the good moral values of the main character in the novel Peter by Risa Saraswati, (2) the bad moral values of the main character in the novel Peter by Risa Saraswati. In addition, it also describes (3) the form of conveying moral values in the novel Peter by Risa Saraswati. This research is a qualitative descriptive study. The data source of this research is the novel Peter by Risa Sarswati. The results of the analysis of this study indicate that the main character's moral values show (1) good moral values that include a. Religious b. caring c. Responsible d. Confident e. Compassionate f. Mannerly. (2) bad moral values that include being disrespectful, and rude. (3) Forms of Direct and Indirect Delivery of Moral ValuesKata Kunci: Moral Values, Good Morals, Bad Morals, Forms of Delivery of Moral Values